2023
DOI: 10.3390/en16104035
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of Miniature Scale Liquid Fuel Combustors for Power Generation Application—A Review

Vinay Sankar,
Sreejith Sudarsanan,
Sudipto Mukhopadhyay
et al.

Abstract: As the demand for powerful, light energy sources continues to grow, traditional electrochemical batteries are no longer sufficient and combustion-based power generation devices have become an attractive alternative due to their high energy density, compact size, fast recharging time and long service life. While most research on miniature-scale combustors has focused on gaseous fuels, the use of commonly available liquid fuels has the potential to be highly portable and economical. However, the complexity of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…The study revealed that the flame could be effectively anchored due to flow re-circulation with backward steps, and CH 4 blow-off limits could be further extended owing to the better heat re-circulation in the long preheating channels. Sankar et al [17] studied the application of different techniques for implementing liquid fuels in different types of micro-combustors for power generation. Cai et al [18] introduced a novel micro-disc burner with an annular step by using H 2 as fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that the flame could be effectively anchored due to flow re-circulation with backward steps, and CH 4 blow-off limits could be further extended owing to the better heat re-circulation in the long preheating channels. Sankar et al [17] studied the application of different techniques for implementing liquid fuels in different types of micro-combustors for power generation. Cai et al [18] introduced a novel micro-disc burner with an annular step by using H 2 as fuel.…”
Section: Introductionmentioning
confidence: 99%